The future shapes of Anglicanism: currents, contours, charts - Percy, Martyn (Routledge Contemporary Ecclesiology, 2017)
The future shape of Anglicanism -- Currents, contours, charts -- Growth and management in the Church of England, some charts -- New currents in executive and archiepiscopal leadership -- The emerging contours of archiepiscopal leadership -- Money, sex, and power divisions and diversities -- Future possibilities for funding the ministry of the Church of England -- Spartacus: modelling rebellion in the church -- Power in the church? congregations, churches and the Anglican communion -- Maps and forecasts -- Future directions of travel -- Re-charting the church -- Old maps for new territories -- Back to the future? -- The churchgoer's charter